Strengthening the Constitutional Law System (Legal Challenges and Strategies in Handling the Social, Economic and Political Crisis in Indonesia) - Muhammad Doing; Warriyodi; Darma Kartian; Muhammad Irsyadul Ibad; Aprieyanti; Fitriani (Journal Equity of Law and Governance, 2024)
Indonesia's constitutional legal system faces significant challenges due to ongoing social, economic, and political crises. These challenges stem from issues such as systemic corruption, uneven development, social inequality, and political instability. The legal system must evolve and adapt to address these challenges effectively and equitably. This article examines the impact of crisis policies on legal and governmental stability, with a focus on how constitutional legal systems can adapt to and overcome these obstacles. This study employs normative and conceptual analysis to assess the flexibility, transparency, accountability, and justice within Indonesia's constitutional law. The analysis is grounded in an evaluation of relevant laws and regulations, highlighting how constitutional amendments, decentralisation, and the strengthening of state institutions influence the legal system's responses and overall efficacy. Despite efforts to reform and fortify the judicial system, persistent issues such as widespread corruption, regional disparities, and entrenched social inequalities continue to pose significant challenges. This article underscores the need for crisis-responsive legal policies and offers strategic recommendations to enhance the resilience and adaptability of the legal system. These recommendations include improving mechanisms for monitoring and accountability, developing more inclusive and sustainable policies, and fostering greater community involvement in the legal process.Through this analysis, the study contributes to a deeper understanding of how Indonesia's constitutional legal system can be optimised to address escalating crises and challenges, while promoting more effective and sustainable reforms